Investigação das fases formadas na superfície do aço inoxidável AISI 316L nitretado a plasma - Campos, Marcelo (2013)
The plasma nitriding treatment improves mechanical, tribological and corrosion resistance, due to the formation of a nitrided layer consisting of an iron and chromium nitrides and a phase, with an undefined structure, known as expanded austenite (γN). The layer properties are influenced by the nitriding parameters, and the aim of this thesis is to study the influence of gas nitriding pressure in AISI 316L stainless steel. For this purpose, samples of this material were nitrided during 4 hour at 400 ºC in 80% H2 and 20% N2 atmosphere under variable pressures (3 and 7 Torr). Optical and Scanning Electron Microscopy, Vickers microhardness, cytotoxicity, roughness and wear tests, Mössbauer spectroscopy (MS) and X-ray diffraction (XRD) were used to analyze the mechanical, tribological, structural and potential application as a biomaterial in the nitrided samples. The results showed that the halo´s width, formed due to edge effect in the edge sample region, decreases with pressure increase, while their mechanical and tribological properties are not influenced. In the others samples regions, the layer thickness, surface roughness and mass loss reduction in wear test increased with pressure increase until 6 Torr sample and the surface hardness increased with pressure. MS techniques and the grazing angle XRD showed the same phases formed: γN, ε, α-FeNi and ε-Fe2+XN in all samples and also α"-Fe16N2, δ-Fe2N phase in 5-7 Torr samples. These phases indicated that the iron nitrides are responsible for the increase in surface hardness and coefficient of friction increased, where the reduction of ε phase concentration increases the coefficient value. The XRD fits shows that the most appropriate γN structure is FCC with stacking faults with nitrogen concentration depth distribution. This distribution and structure, explain the anomalous large expansion and position in the (200) plane, respectively. The cytotoxicity test showed that the nitrided did not present any toxic effect. The sample nitrided at 6 Torr showed the best combined nitriding properties.